Level of Satisfaction of Ecotourism Visitors Mempawah Mangrove Park - Halidi, Fahmi; Dolorosa, Eva; Imelda, Imelda (Jurnal Sains Mahasiswa Pertanian, 2019)
Ecotourism is nature-based tourism that is related to education and understanding of the natural environment and managed with sustainable principles. Ecotourism visitors also need satisfaction when visiting an ecotourism, ecotourism managers must be able to understand the needs of visitors and try to fulfill them so that visitors can achieve satisfaction and will have a positive impact on increasing the number of visitors. The research objective is to measure the level of visitors satisfaction on Mempawah Mangrove Park ecotourism. The research was conducted in the Mempawah Mangrove Park area, Pasir Village, Mempawah Hilir Subdistrict, Mempawah District. The sampling method was used accidental sampling with a sample of 96 respondents. The analytical method used to is the Importance Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). The CSI results are of 74,89 % means that visitors are satisfied with the performance of Mempawah Mangrove Park